PENGALAMAN KERJA SEBAGAI PROSES BELAJAR - Saukani; Ade Taufan; Ansori (Hira Institute, 2024)
This service is motivated by the lack of work experience carried out by students in tertiary institutions, even though work experience is very helpful for students who will enter the world of work, the method of implementing this service is carried out using a discussion and question and answer system, while the results of this service are around 90% of students who are able to understand and know how important work experience is